Apprehension to Application: How a Family Science Night Can Support Preservice Elementary Teacher Preparation - Feille, Kelly; Shaffery, Heather (Innovations in Science Teacher Education, 2020)
Preservice elementary teachers (PSETs) often have limited opportunities to engage as teachers of science. As science-teacher educators, it is important to create experiences where PSETs can interact with science learners to facilitate authentic and engaging science learning. Using informal science learning environments is one opportunity to create positive teaching experiences for PSETs. This manuscript describes the use of a Family Science Night during an elementary science methods course where PSETs are responsible for designing and facilitating engaging science content activities with elementary students.